The Role of Systemic Immune-Inflammation Index on The Clinical Degree of Dengue Hemorrhagic Fever Patients at Bethesda Hospital Yogyakarta - Amumpuni, Antonia Namelia Wahyu; Sooai, Christiane Marlene; Priskila, Loury; Wicaksono, Hendi; Probowati, Wiwiek (MEDICINUS, 2025)
Background: Dengue hemorrhagic fever (DHF) is a mosquito-borne infectious disease caused by the dengue virus and transmitted primarily by Aedes aegypti. According to the World Health Organization (WHO), DHF remains a major globalhealth concern, particularly in tropical and subtropical regions. The disease can result in severe complications, including hemorrhage and hypovolemic shock, which may lead to death. Despite ongoing vector control initiatives, DHF continues to pose a significant public health challenge, especially in areas with inadequate sanitation and limited healthcare infrastructure.Objectives: To evaluate the role of systemic immune-inflammation index (SII) in determining the clinical severity of denguehemorrhagic fever (DHF) among patients at Bethesda Hospital Yogyakarta.Methods: This was a cross-sectional study utilizing medical records from 333 DHF patients at Bethesda Hospital Yogyakarta. Records were screened based on predefined inclusion and exclusion criteria. A total of 172 eligible cases were selected using odds ratio-based sample size calculations. Consecutive sampling was employed as the samplingtechnique. Data analysis was performed using SPSS and Microsoft Excel to determine statistical significance.Results: The findings demonstrated that neutrophil, lymphocyte, and platelet counts significantly influenced the clinical severity of dengue hemorrhagic fever (DHF). Chi-square analysis revealed a statistically significant association between the systemic immune-inflammation index (SII) and disease classification (DF/DHF) (p<0.001). However, the relationshipbetween SII levels and clinical severity did not follow a linear pattern. Contrary to established theories—where elevated SII values are typically associated with increased disease severity—this study observed variations that may be attributed toconfounding factors such as patient age, comorbidities, and individual immune response.Conclusion: The systemic immune-inflammation index (SII) is significantly associated with the clinical severity of DHF in patients at Bethesda Hospital Yogyakarta, although its correlation may be influenced by additional patient-specificvariables such as patient age, comorbidities, and individual immune responses.Keywords: systemic immune-inflammation index (SII), dengue hemmorhagic fever (DHF), dengue severity, clinicalseverity.